2009
DOI: 10.3802/jgo.2009.20.1.60
|View full text |Cite
|
Sign up to set email alerts
|

A case of clear cell carcinoma arising from the endometriosis of the paraovarian cyst

Abstract: Malignant transformation of endometriosis is an infrequent complication. Clear cell carcinoma from endometriosis is very rare in the paraovarian cyst. To date no cases have been reported. We report a case of clear cell carcinoma arising from endometriosis of the paraovarian cyst with a brief review of literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…A statistically significant negative correlation between BMPR2 and BMP-2 concentrations, demonstrated through the absence of a statistically significant correlation between the concentrations of this receptor and BMP-7, may suggest that the BMPR2 receptor has a greater affinity for the BMP-2 molecule than BMP-7. Lee et al [18] observed that bone morphogenetic protein receptors present on the surface of cells, before binding to the soluble form of the ligand, occur in the form of homomeric, as well as heteromeric, complexes and have low expression. However, upon ligand attachment, most BMP receptors form heteromeric complexes, and the expression of these receptors significantly increases.…”
Section: Discussionmentioning
confidence: 99%
“…A statistically significant negative correlation between BMPR2 and BMP-2 concentrations, demonstrated through the absence of a statistically significant correlation between the concentrations of this receptor and BMP-7, may suggest that the BMPR2 receptor has a greater affinity for the BMP-2 molecule than BMP-7. Lee et al [18] observed that bone morphogenetic protein receptors present on the surface of cells, before binding to the soluble form of the ligand, occur in the form of homomeric, as well as heteromeric, complexes and have low expression. However, upon ligand attachment, most BMP receptors form heteromeric complexes, and the expression of these receptors significantly increases.…”
Section: Discussionmentioning
confidence: 99%